Coexistence of Culture of Ethnic Groups in Vietnam for the Development of Thai Human Resources - Muenjanchoey, Renu; Srichumpa, Sophana; Thongdee, Iam (Parichart Journal, 2024)
This article aimed to report the coexistence culture of major ethnic groups in ASEAN society for the human resource development of Thailand. The study systematically collected data from various sources, including documents, books, research reports, and articles. The data were rigorously selected based on representativeness. The research revealed that after Vietnam’s reunification into the Socialist Republic, various ethnic groups continued to coexist in shared areas. Groups previously aligned with South Vietnam, such as the Khmer, Cham, and Tai-Tai, were subject to managed coexistence policies by the Vietnamese government. These policies mandated designated living areas and limited rights, contrasting with groups historically aligned with the Communist Party. Subsequently, government initiatives post-reunification, including the “Doi Moi” policy shift, aimed at fostering economic development and equitable coexistence. This approach aimed to equalize opportunities, particularly benefiting the Viet (Kinh) and Chinese ethnic groups, which possessed economic capital, foreign networks, and prior experience. On the other hand, the Tai-Tai, Cham, and Khmer groups faced socio-economic challenges while contributing to local development and supporting businesses at community levels. These findings provide valuable insights and lessons for Thai society and the ASEAN community. They underscore the importance of formulating inclusive policies and measures to promote equality, fairness, and sustainable coexistence among ethnic groups within and across societies.